Serum Levels of Cardiac Markers NT-proANP and NT-proBNP in Brachycephalic bitches at Different Gestational Stages - Feliciano, M. A.R. [UNESP]; Uscategui, R. R. [UNESP]; Maciel, G. S. [UNESP]; de Almeida, V. T. [UNESP]; Silveira, M. F. [UNESP]; de Oliveira, G. A.C. [UNESP]; Vicente, W. R.R. [UNESP] (Wiley, 2016)
The aim of this study was to determine serum levels of natriuretic peptide precursors (NT-proANP and NT-proBNP) during pregnancy in brachycephalic bitches. Fifteen healthy multiparous bitches were selected for this prospective study. Serum levels of NT-proANP and NT-proBNP were measured during anoestrous and at 14, 35, 42, 49 and 56 days (2nd, 5th, 6th, 7th and 8th weeks) of pregnancy. Fourteen animals had normal gestations, and one bitch developed single foetus syndrome. The natriuretic peptide levels of this animal were not included in this study; however, it is important to report that its NT-proANP levels were four times greater than those of normal patients. There was no significant difference (p = 0.072) in NT-proBNP levels between anoestrous (0.20 ± 0.10 ng/ml) and the different pregnancy weeks (0.27 ± 0.12 ng/ml). There was a positive correlation (p < 0.0001) between NT-proANP and gestational age, and the levels of this marker increased significantly (p < 0.0001) during the 6th (0.26 ± 0.06 ng/ml), 7th (0.28 ± 0.04 ng/ml) and 8th weeks (0.29 ± 0.05 ng/ml) when compared to anoestrous (0.18 ± 0.02 ng/ml). NT-proANP serum levels are correlated with gestational development and may be indicative of cardiovascular adaptation in canine brachycephalic pregnancy.